(3GdJGQjN GdCced (B( (3ef SfI (B501 : 920 (3g` (B)s - (3GdTQja CMeO Hf YHO Gddg Hf Ydhj TfHds ((3YHO Gddg Hf MSjf QMje HGaVd s)
(3ChdgG (B:s
(3hai SfI (B501 (3g` Jhai fLe GdOjf , eMeO Hf Ydi Hf aGQS , GdeYQha HGHf GdeYde GdhGSWi GdYQHi s
(3BNQgG (B:s
(3BNQg CKfGA SfI (B920 (3g` , bhdg (B:" (3hajgG Jhai GdTQja Rjf GdYGHOjf Hf eMeO Hf GdTjN Ydi Hf CHj HcQ s
(3cJHJ HQSe eMeO Hf YHO GdbGOQ HGabjgs
(3hfbdJ Yf fSNI YdjgG bQGAI eGdcgG GdYGQa HGddg CMeO Hf MSf Hf YHO Gddg GdYWGS SfI (B1321 (3g`s
(3hJYhO bjeI gPg GdfSNI Edi Cf GdCUd (B- (3ceG bjd (B_ (3eabhOs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI eJMa GdecdG ddBKGQ GdecdG s
Keywords: (3GdJGQjNs